2015
DOI: 10.1007/s13546-015-1033-y
|View full text |Cite
|
Sign up to set email alerts
|

Le syndrome thoracique aigu : complication pulmonaire aiguë des patients adultes atteints d’un syndrome drépanocytaire majeur

Abstract: Le syndrome thoracique aigu (STA) est une des complications majeures des syndromes drépanocytaires et reste la principale cause de mortalité chez l'adulte. Il peut survenir chez des patients auparavant peu ou non symptomatiques, notamment chez ceux porteurs d'un syndrome drépa-nocytaire composite. Trois grandes causes dominent les étio-logies : les infections, l'obstruction vasculaire pulmonaire (par des emboles graisseux et/ou des thrombi fibrinocruoriques) et les hypoventilations alvéolaires secondaires à de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Nansseu et al [11] had found results that are superior to ours with an average CRP value of 228.4 mg/dl and extremes ranging from 4.5 to 432 mg/dl but lower than those of Lebouc et al [13] who found an average CRP of 88 mg/dl. The increase in CRP is therefore almost constant during ATS and is not synonymous with bacterial infection [17].…”
Section: Paraclinical Aspectsmentioning
confidence: 97%
See 1 more Smart Citation
“…Nansseu et al [11] had found results that are superior to ours with an average CRP value of 228.4 mg/dl and extremes ranging from 4.5 to 432 mg/dl but lower than those of Lebouc et al [13] who found an average CRP of 88 mg/dl. The increase in CRP is therefore almost constant during ATS and is not synonymous with bacterial infection [17].…”
Section: Paraclinical Aspectsmentioning
confidence: 97%
“…Only one patient (0.98%) presented with pleural effusion syndrome. Indeed, it has been described that parenchymal involvement is sometimes associated with pleural involvement in severe forms [17].…”
Section: Clinical Aspectsmentioning
confidence: 99%